Evaluating The Economy Growth by Supply Chain Strategies and Testing the Validity of Okun’s Laws in Indonesia - Didit Purnomo; Nungki Kusumastuti; Muhammad Anas; Siti Aisyah; Mohd Shahidan Shaari (International Journal of Supply Chain Management, 2020)
Abstract- With globalization and integration of the world economy, the concept of extended enterprise has taken root, leading to an increasingly important role played by the entire supply chain management, including procurement, logistics and distribution for ensuring a consistently high degree of customer satisfaction in terms of quality, delivery and cost. Unemployment is one of the main problems in developing countries, including Indonesia. This study aims to evidence the state pattern of the relationship between unemployment, supply chain strategy, and economic growth by investigating the accuracy of the Okun’s Law and the Phillips’ Curve in Indonesia. Time series data are sourced from the World Bank. As an addition to the independent variable, the dependency ratio is acknowledged to investigate unemployment based on the premise that a high dependency ratio will reduce the unemployment rate. The analysis model used in this study is the Error Correction Model (ECM). The results of this study are inflation rates, economic growth, and dependency ratios attained to be positively related to unemployment, and it illustrates that the Okun’ Law and Phillips’ Curve are not accurate to be applied in Indonesia.